Peran Kurikulum Berbasis Kompetensi untuk Meningkatkan Mutu Pendidikan di Lembaga Pendidikan Menengah - Eldina Sarah Nababan (Jurnal Ilmu Pendidikan dan Sosial, 2024)
Competency-based curriculum has become the main focus in efforts to improve the quality of education. This approach emphasizes the development of skills, knowledge and attitudes that are relevant to real world needs. By adapting learning to student needs and job market demands, competency-based curricula can help improve the quality of education and prepare students for future challenges. The aim of this research is to identify the role of competency-based curriculum in improving the quality of education in secondary education institutions. The research method used is descriptive research, with library research or literature study. The data sources taken are books, research journals or scientific journals that discuss competency-based curricula. Data collection was carried out through literature searches using basic data. The data collected can be analyzed to find findings or themes and patterns according to the focus of the discussion. The competency-based curriculum is a curriculum that has the potential to improve the quality of education in Indonesia. With KBK students are encouraged to learn with their personal competencies which are used as a whole in achieving learning goals or educational goals.